Development and implementation of an injury and illness surveillance system for team USA - Post, E. G.; Anderson, T.; Samson, O.; Gidley, A. D.; Triplett, A. N.; Donaldson, A. T.; Finnoff, J. T.; Adams, W. M. (Injury Epidemiology, 2025)
Background The purpose of this report is to provide insight and details regarding the development and implementation of an injury and illness surveillance (IIS) system for the United States Olympic and Paralympic Committee (USOPC).